Synthesis of retinal ganglion cell phospholipids is under control of an endogenious circadian clock: Daily variations in phospholipid-synthesizing enzyme activities - Garbarino Pico, Eduardo (2004)
Retinal ganglion cells (RGCs) are major components of the vertebrate circadian system. They send information to the brain, synchronizing the entire organism to the light-dark cycles. We recently reported that chicken RGCs display daily variations in the biosynthesis of glycerophospholipids in constant darkness (DD). It was unclear whether this rhythmicity was driven by this population itself or by other retinal cells. Here we show that RGCs present circadian oscillations in the labeling of [32P]phospholipids both in vivo in constant light (LL) and in cultures of immunopurified embryonic cells. In vivo, there was greater [32]orthophosphate incorporation into total phospholipids during the subjective day. Phosphatidylinositol (PI) was the most 32P-labeled lipid at all times examined, displaying maximal levels during the subjective day and dusk. In addition, a significant daily variation was found in the activity of distinct enzymes of the pathway of phospholipid biosynthesis and degradation, such as lysophospholipid acyltransferases (AT II), phosphatidate phosphohydrolase (PAP), and diacylglycerol lipase (DGL) in cell preparations obtained in DD, exhibiting differential but coordinated temporal profiles. Furthermore, cultures of immunopurified RGCs synchronized by medium exchange displayed a circadian fluctuation in the phospholipid labeling. The results demonstrate that chicken RGCs contain circadian oscillators capable of generating metabolic oscillations in the biosynthesis of phospholipids autonomously.